Let this be our secret : the shocking true story of a killer dentist, his mistress, how they murdered their spouses–and how they almost got away with it /: the shocking true story of a killer dentist, his mistress, how they murdered their spouses–and how they almost got away with it. (2011) - Unknown
No abstract available